2004
DOI: 10.1016/j.febslet.2004.06.070
|View full text |Cite
|
Sign up to set email alerts
|

Localization and mutagenesis of the sorting signal binding site on sortase A from Staphylococcus aureus

Abstract: Surface proteins in Gram-positive bacteria are anchored to the cell wall by the action of sortase enzymes. The Staphylococcus aureus sortase A (SrtA) protein anchors proteins by recognizing a cell wall sorting signal containing the amino acid sequence LPXTG. To understand how SrtA binds this sequence, we carried out NMR studies of new peptidylcyanoalkene and peptidyl-sulfhydryl inhibitors that contain the sorting signal sequence LPAT. These studies combined with amino acid mutagenesis identified a catalyticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 32 publications
1
59
0
1
Order By: Relevance
“…Previously, we assigned the backbone chemical shifts of the SrtA ⌬N59 protein in the complex (29). In this report, to solve the structure of the complex, we assigned nearly all of the 1 H, 13 C, and 15 N chemical shifts of the protein and the 1 H chemical shifts of the bound peptide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we assigned the backbone chemical shifts of the SrtA ⌬N59 protein in the complex (29). In this report, to solve the structure of the complex, we assigned nearly all of the 1 H, 13 C, and 15 N chemical shifts of the protein and the 1 H chemical shifts of the bound peptide.…”
Section: Resultsmentioning
confidence: 99%
“…Wild-type SrtA from S. aureus containing amino acid residues 60 -206 (SrtA ⌬N59 ) was produced as described previously (29). Uniformly 15 N-and 13 C-or 15 N-labeled SrtA ⌬N59 protein was covalently attached to an analog of the LPXTG sorting signal, Cbz-LPAT* (where T* is (2R,3S)-3-amino-4-mercapto-2-butanol, and Cbz is a carbobenzyloxy protecting group).…”
Section: Preparation Of the Covalent Complex For Nmr Studies-mentioning
confidence: 99%
“…This cation, present in millimolar amounts in host tissues, activates sortase activity eightfold (84). Analysis of the sortase NMR spectra in the presence and absence of calcium revealed that Glu 105 , Glu 108 , and Asp 108 side chains of the ␤3-␤4 loop interact with the cation. In contrast, the ␤6-␤7 loop forms a flap that is disordered in the absence of calcium (131,227).…”
Section: Sortase a Structurementioning
confidence: 99%
“…Leucine and proline residues of the LPETG peptide are bound in the C-terminal region of ␤7, surrounded by several highly hydrophobic residues (228). NMR analysis of the 1 H-15 N chemical shifts of sortase in the presence or absence of ligand allowed identification of residues that comprise the LPXTG binding surface (108). Residues perturbed after ligand binding also mapped to the C-terminal region of the ␤7 strand (Thr 180 and Ile 182 ) and to the vicinity of the loop connecting strands ␤3 and ␤4 (Ala 118 ).…”
Section: Sortase a Structurementioning
confidence: 99%
See 1 more Smart Citation